Application of shearband boudins analysis to understand ductile shear zones - Sousa, João P. (2011)
The methodology used for the kinematic analysis of H-T ductile shear zones based on geometric analysis of boudins, proved to be a easy application tool. The boudin analysis begans with the measurement of the Lb (boudin axis) orientation, as a fundamental element of the kinematic analysis in simple shear – Lb proved always to be perpendicular to a local displacement plane (Sx) that is defined as the plane that contains different lineations (e.g., stretching lineation in the host rock) and so, validates the orientation of the outcrop plane. The methodology also includes the measurement of several angular and dimensional parameters. The main objective of this study deals with the validation of the broad utility of this methodology in shear zones with different P-T conditions. It was studied a shearband boudin field on a Grt-St shear zone, which was compared with previous studies on Sil shear zone.